2009
DOI: 10.1002/elsc.200800049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal in constructed wetland systems

Abstract: Since the mid 1990s, constructed wetlands have been increasingly used as a low‐energy ‘green’ technique, in the treatment of wastewater and stormwater, driven by the rising cost of fossil fuels and increasing concern about climate change. Among various applications of these wetlands, a significant area is the removal of nitrogenous pollutants to protect the water environment and to enable effective reclamation and reuse of the wastewater. This paper provides a review of the current state of nitrogen removal te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
184
2
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(207 citation statements)
references
References 91 publications
9
184
2
12
Order By: Relevance
“…The condition of anoxic region was probably not favoured in the output final WC due to the lower concentration of nitrate ions which reduces the action of denitrifying microorganisms [53].…”
Section: Resultsmentioning
confidence: 99%
“…The condition of anoxic region was probably not favoured in the output final WC due to the lower concentration of nitrate ions which reduces the action of denitrifying microorganisms [53].…”
Section: Resultsmentioning
confidence: 99%
“…During the exponential growth phase both ammonia-N and nitrate-N concentrations decreased rapidly in the planted wetlands. This was due to both plant uptake and denitrification [21]. However, plant uptake is only between 0 -5% [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, as Flanders is a densely populated region with over 460 inhabitants per km 2 , conflicting demands among various types of land use must be considered. In this region Constructed Wetlands (CWs) have been extensively used for the treatment of urban, industrial, and dairy wastewater [9]; though none of them have been tested to treat agricultural runoff as compared to other countries such as the United States, Norway, Turkey, Sweden, the Netherlands, among others [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive amounts of nitrogen in water lead to oxygen depletion affecting aquatic life and organisms. Nitrogen could be present in surface water in different forms, but total nitrogen (TN), ammonium nitrogen (NH 4 -N), organic nitrogen, nitrite (NO 2 ), and nitrate (NO 3 ) are the main forms that end up in the surface water [2,3]. Several studies have reported that nitrate and nitrite concentrations in rivers greatly differ from each other, with nitrite concentrations being negligible in most cases.…”
Section: Introductionmentioning
confidence: 99%